Turn. Washington's spies. The complete first season [videorecording (DVD)] - Silverstein, Craig ([publisher not identified], 2015)
A historical thriller set during the Revolutionary War. Abe Woodhull is a farmer living in British-occupied Long Island who bands together with his friends to from the Culper Ring, an unlikely team of secret agents who not only went on to help George Washington turn the tide of the war, but also gave birth to modern spycraft.